2009
DOI: 10.1097/mjt.0b013e31816b69bc
|View full text |Cite
|
Sign up to set email alerts
|

Does Synchronizing Initiation of Therapy Affect Adherence to Concomitant Use of Antihypertensive and Lipid-Lowering Therapy?

Abstract: Although efficacious medications are available to treat hypertension and dyslipidemia, treatment adherence is often poor. This retrospective study evaluated adherence in patients newly initiating antihypertensive (AH) and lipid-lowering (LL) therapies simultaneously versus within 180 days of one another. Data were analyzed for US managed care plan enrollees initiating AH before LL (cohort 1;n = 7099), LL before AH (cohort 2; n = 3229), or AH/LL simultaneously (cohort 3; n = 5072). A multivariate model evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…In the Patel et al [22] study, patients taking single-pill amlodipine atorvastatin were almost twice as likely to be adherent compared with those taking a twopill amlodipine and atorvastatin regimen, and nearly three times more likely to be adherent than those taking other two-pill CCB and statin regimens at 6 months, with a greater benefit after 1 year of follow-up. Since there is no known difference in efficacy or tolerability between single-pill amlodipine atorvastatin and treatment with coadministered amlodipine and atorvastatin, [20,21,33,34] it is likely that these adherence benefits are related to other factors associated with single-pill therapy, such as a lower pill burden, [1,16,35] synchronization of therapy initiation, [1,19] or reduced co-payment costs, [17,18] all of which have been demonstrated to influence adherence in previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Patel et al [22] study, patients taking single-pill amlodipine atorvastatin were almost twice as likely to be adherent compared with those taking a twopill amlodipine and atorvastatin regimen, and nearly three times more likely to be adherent than those taking other two-pill CCB and statin regimens at 6 months, with a greater benefit after 1 year of follow-up. Since there is no known difference in efficacy or tolerability between single-pill amlodipine atorvastatin and treatment with coadministered amlodipine and atorvastatin, [20,21,33,34] it is likely that these adherence benefits are related to other factors associated with single-pill therapy, such as a lower pill burden, [1,16,35] synchronization of therapy initiation, [1,19] or reduced co-payment costs, [17,18] all of which have been demonstrated to influence adherence in previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…hypertension), [13][14][15] potentially as a result of reduced pill burden, [1,16] decreased co-payment costs to the patient, [17,18] and the synchronization of therapies so that medications are prescribed at the same time. [1,19] The single-pill combination of amlodipine and atorvastatin is the first approved combination tablet formulated to treat multiple risk factors for cardiovascular disease. [20,21] A previous study among 4703 patients has demonstrated that patients receiving single-pill amlodipine atorvastatin were more than twice as likely to achieve adherence to both antihypertensive and statin therapy compared with patients receiving amlodipine and atorvastatin as separate pills.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a US managed-care setting, initiating lipid-lowering and antihypertensive therapy together increased adherence to both classes of medication by 34%, compared with patients who started their medications 2-3 months apart. [40,41] The new generation of combined pills, targeting one or more cardiovascular risk factors, is expected to be useful in this regard, and it will be interesting to see whether their availability has any effect on prescribing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in tandem with what had been reported in the past by other researchers. [4][5][6]2 Prominent among the factors that could affect adherence to therapy are cost of drugs, polypharmacies, dissatisfaction with healthcare providers and long waiting time.…”
Section: 22-24mentioning
confidence: 99%
“…Some past studies have reported adherence to antihypertensive treatment ranging from 36% to 49%. [4][5][6]2 Addressing the problem of adherence to therapy among hypertensive patients will require a multi-dimensional approach, one of which is analysis of the cost of the drugs. Economic analysis of the cost of treatment is the domain of pharmacoeconomics.…”
Section: Introductionmentioning
confidence: 99%